Estudio de prefactibilidad para la instalación de una planta productora de grafeno usado como aditivo para concreto a base de residuos orgánicos y plásticos - Cribillero Meza, Claudia Vanessa (2022)
The construction sector in Peru is one of the most important economic activities in the country. The production of ready mixed concrete is critical in the making of many structures, but this activity possess limitations, such as high fragility and low capacity of deformation. In addition, it exhibits some spoiled process which results in the formation of fissures, expansion or cracking. In this way, we propose including graphene as an additive to concrete. Its application brings an increase on endurance to compression and flexibility, electric and thermic performance and minimizes its permeability to water in 60% in comparison to standard concrete, making structures last longer. This investigation project evaluates de technological and economic pre-feasibility of the installation of a factory of graphene used as an additive for concrete produced with organic waste and plastic. For this, a market study has been made in order to determine the demand of the project and establish the marketing strategies taking the objective public in consideration. Then, the location and plant capacity are determined. After this, we proceed with the engineering part, where it is decided the product specifications, the technology and machines to use and the installed capacity, the minimum requirements and plant disposition. Later on, it is discussed the formation of the company, the employees needed in order for the factory to run and their roles. Finally, the economic, financial and social viability of the project is evaluated.